MCOLN1/TRPML1 finely controls oncogenic autophagy in cancer by mediating zinc influx. Issue 12 (2nd December 2021) - Qi, Jiansong; Xing, Yanhong; Liu, Yucheng; Wang, Meng-Meng; Wei, Xiangqing; Sui, Zhongheng; Ding, Lin; Zhang, Yang; Lu, Chen; Fei, Yuan-Hui; Liu, Nan; Chen, Rong; et al.
ABSTRACT: Macroautophagy/autophagy is elevated to ensure the high demand for nutrients for the growth of cancer cells. Here we demonstrated that MCOLN1/TRPML1 is a pharmaceutical target of oncogenic autophagy in cancers such as pancreatic cancer, breast cancer, gastric cancer, malignant melanoma, and glioma. First, we showed that activating MCOLN1, by increasing expression of the channel or using the MCOLN1 agonists, ML-SA5 or MK6-83, arrests autophagic flux by perturbing fusion between autophagosomes and lysosomes. Second, we demonstrated that MCOLN1 regulates autophagy by mediating the release of zinc from the lysosome to the cytosol. Third, we uncovered that zinc influx through MCOLN1 blocks the interaction between STX17 (syntaxin 17) in the autophagosome and VAMP8 in the lysosome and thereby disrupting the fusion process that is determined by the two SNARE proteins. Furthermore, we demonstrated that zinc influx originating from the extracellular fluid arrests autophagy by the same mechanism as lysosomal zinc, confirming the fundamental function of zinc as a participant in membrane trafficking. Last, we revealed that activating MCOLN1 with the agonists, ML-SA5 or MK6-83, triggers cell death of a number of cancer cells by evoking autophagic arrest and subsequent apoptotic response and cell cycle arrest, with little or no effect observed on normal cells. Consistent with the in vitro results, administration of ML-SA5 in Patu 8988 t xenograft mice profoundly suppresses tumor growth and improves survival. These results establish that a lysosomal cation channel, MCOLN1, finely controls oncogenic autophagy in cancer by mediating zinc influx into the cytosol. Abbreviation: Abbreviations: 3-MA: 3-methyladenine; AA: amino acid; ATG12: autophagy related 12; Baf-A1: bafilomycin A1; BAPTA-am: 1, 2-bis(2-aminophenoxy)ethane-N, N, N', N'-tetraacetic acid tetrakis-acetoxymethyl ester; co-IP: coimmunoprecipitaion; CQ: chloroquine; DMEM: Dulbecco's Modified Eagle Medium; FBS: fetal bovine serum; GAPDH: glyceraldehyde- 3-phosphate dehydrogenase; HCQ: hydroxychloroquine; HEK: human embryonic kidney; LAMP1: lysosomal associated membrane protein 1; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MCOLN1/TRPML1: mucolipin TRP cation channel 1; MTORC1: mechanistic target of rapamycin kinase complex 1; NC: negative control; NRK: normal rat kidney epithelial cells; PBS: phosphate-buffered saline; PtdIns3K: phosphatidylinositol 3-kinase; RPS6KB/S6K: ribosomal protein S6 kinase B; shRNA: short hairpin RNA; siRNA: short interfering RNA; SNARE: soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein receptor; SQSTM1/p62: sequestosome 1; STX17: syntaxin 17; TPEN: N, N, N', N'-tetrakis(2-pyridylmethyl)ethylenediamine; TTM: tetrathiomolybdate; ULK1: unc-51 like autophagy activating kinase 1; VAMP8: vesicle associated membrane protein 8; Zn 2+ : zinc.